2013
DOI: 10.1186/1471-2407-13-411
|View full text |Cite
|
Sign up to set email alerts
|

Stromal matrix metalloprotease-13 knockout alters Collagen I structure at the tumor-host interface and increases lung metastasis of C57BL/6 syngeneic E0771 mammary tumor cells

Abstract: BackgroundMatrix metalloproteases and collagen are key participants in breast cancer, but their precise roles in cancer etiology and progression remain unclear. MMP13 helps regulate collagen structure and has been ascribed largely harmful roles in cancer, but some studies demonstrate that MMP13 may also protect against tumor pathology. Other studies indicate that collagen’s organizational patterns at the breast tumor-host interface influence metastatic potential. Therefore we investigated how MMP13 modulates c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 65 publications
4
21
0
Order By: Relevance
“…Furthermore, we have previously shown that altering the availability of stromal MMP-13 altered F/B and metastatic output. 18 The fact that tumor cells themselves can affect F/B (as shown here), and that alteration of enzymes present in the stroma can alter F/B (as shown previously), suggests that both tumor and stromal cells play key roles in defining the matrix microstructure that dictates F/B.…”
supporting
confidence: 73%
“…Furthermore, we have previously shown that altering the availability of stromal MMP-13 altered F/B and metastatic output. 18 The fact that tumor cells themselves can affect F/B (as shown here), and that alteration of enzymes present in the stroma can alter F/B (as shown previously), suggests that both tumor and stromal cells play key roles in defining the matrix microstructure that dictates F/B.…”
supporting
confidence: 73%
“…It has been reported that MMP13 is related to cancer aggressiveness in hepatocellular carcinoma [27]. Stromal MMP13 mediates tumor microenvironment and promotes lung metastasis of breast cancer [28]. In the present study, expression level of MMP13 was found to be decreased under condition of CCR4 knockdown, while overexpression of CCR4 increased the level of MMP13 in tumor cells.…”
Section: Discussionsupporting
confidence: 52%
“…It has been reported that MMP13 is involved in cancer metastasis in hepatocellular carcinoma . Stromal MMP13 is involved in tumor microenvironment and promotes lung metastasis of breast cancer . In our study, expression level of p‐ERK and MMP13 was found to be decreased under conditions of CCR4 knockdown in BC cells.…”
Section: Discussionsupporting
confidence: 54%